Evaluasi Program Pembinaan Guru Pamong Community Learning Center (CLC) SMP Sabah di Sekolah Indonesia Kota Kinabalu - Higar Iman Pribadi; Lia Yuliana (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to evaluate the tutor teacher development program of the Sabah Junior High School Community Learning Center (CLC) under the auspices of the Indonesian School of Kota Kinabalu (SIKK) based on the context, input, process, and product (CIPP) aspects. This study employed an evaluative approach with the CIPP model and a qualitative descriptive method. The research was conducted at the Indonesian School of Kota Kinabalu, with research subjects comprising the school principal, the program organizing committee, and the tutor teachers of the Sabah Junior High School CLC. Data collection techniques were carried out through interviews, observation, and documentation, while data analysis utilized the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that in the context aspect, the development program has a high level of relevance to the needs of tutor teachers in the Sabah CLC, demonstrated by high participant attendance and alignment with the requirements for enhancing teachers' pedagogical competence. In the input aspect, the program is supported by relevant training materials, competent speakers, varied learning methods, adequate infrastructure, and budget management that supports activity implementation. In the process aspect, the implementation of the development program runs systematically, structurally, and according to planning through active and participatory approaches, although there are constraints regarding limited time and varying levels of participant understanding, which are overcome through coordination and mentoring. In the product aspect, the program yields instructional products in the form of learning posters, worksheets, and experimental designs, and delivers a positive impact toward improving pedagogical competence and more interactive, student-centered teaching practices. Overall, the tutor teacher development program at the Sabah Junior High School CLC is assessed as effective in enhancing teacher competence and supporting learning quality within the CLC environment.